THE LEXICAL COMPARISON BETWEEN TEBING TINGGI SUB-DIALECT IN DHARMASRAYA AND THE STANDARD MINANGKABAUNESE - Faizah Mujahidaturrahmah; Saunir Saun (English Language and Literature, 2018)
The purpose of this research was (1) to identify the lexical differences of Tebing Tinggi sub-dialect in Dharmasraya compared to the standard Minangkabaunese (2) to identify the lexical similarities between Tebing Tinggi sub-dialect and the standard Minangkabaunese. In this paper the researcher used descriptive method; it is possible to compare two dialects so that we can found the differences, the uniqueness of lexical changes, and the vocabulary similarities. From the research that has been done, the researcher used 127 sample data to see the lexical differences and similarities that exist in Tebing Tinggi sub-dialect compared to the standard Minangkabaunese. From the sample the researcher found that Tebing Tinggi sub-dialect often use phoneme /o/ at the first syllable of the word compared to the standard Minangkabaunese that often use phoneme /a/, phoneme /r/ in the standard Minangkabaunese changes to /w/ and /y/ in the middle of the word, and phoneme /a/ changes to /au/ and /iu/ at the end of the word; and from the sample data the researcher also found the similarities in some vocabulary used by Tebing Tinggi sub-dialect and the standard Minangkabaunese. From this paper the researcher hope that this paper can be useful in learning as an additional knowledge in learning Dialectology.